APPLICATION OF THE COLD PLASMA OF GLIDARC TYPE TO THE TREATMENT OF WASTEWATERS FROM SLAUGHTERHOUSES: ABATEMENT OF PHOSPHATES AND NITRATES - Gongwala, Jourdin; Fotio, Daniel; Abba, Paltahe; Payom, Gaston; Laminsi, Samuel; Njopwouo, Daniel (European Scientific Journal, ESJ, 2014)
Acidified and non acidified samples of wastewaters from the Etoudi’s slaughterhouse (Yaounde, Cameroon) were analyzed before and after having been exposed to an electric discharge in a cold plasma reactor at different exposure times. Analyses reveal that untreated and non acidified wastewaters (pH = 7.8) contain 230.4 mgL-1 of phosphate (PO4 3-) and 479.6 mgL-1 of nitrate (NO3 -) ions. Exposure of these wastewaters to the gliding discharge (“glidarc”) operated in humid air induces PO4 3- and NO3 - concentrations abatement by 41.55% for phosphates and 86.24% for nitrates within 20 min of exposure for a gas flow rate of 800 Lh-1,which confirms the efficiency of the glidarc treatment in humid air in case of waste treatments. On the other hand, exposure of acidified wastewaters (pH = 2.2) to the glidarc in the same conditions showed that PO4 3- andNO3 - concentrations increase with exposure time; this result is in conformity with oxidation phenomena induced by the glidarc and previously presented by several authors. From these results the efficiency of the “glidarc” technique in degrading phosphates and nitrates in basic medium was proven.